ES enerģētikas drošība: sadarbība ar Azerbaidžānu, Kazahstānu un Turkmenistānu - Balode, Egita (Latvijas Universitāte, 2011)
Darba tēma ir „Eiropas Savienības enerģētikas drošība: sadarbība ar Azerbaidžānu, Kazahstānu un Turkmenistānu.” Ņemot vērā pieaugošo ES atkarību no Krievijas energoresursu piegādēm, ES strādā pie kopējas enerģētikas politikas izveides un meklē jaunas piegādātājvalstis ar mērķi diversificēt piegādes. Kā vieni no potenciālajiem piegādātājiem tiek minētas Kaspijas jūras reģiona valstis. Darba mērķis bija noskaidrot, vai ES sadarbība ar Azerbaidžānu, Kazahstānu un Turkmenistānu stiprina ES enerģētikas drošību.

The present paper is entitled „Energy Security of European Union: cooperation with Azerbaijan, Kazakhstan and Turkmenistan.” The EU’s largest energy supplier is Russia. In 2006 Russia temporally interrupted natural gas supplies to Ukraine leaving also some of the EU’s members without energy supplies. Through this move Russia lost its status of a reliable supplier. The EU started to work on a common energy policy and in order to diversify its supplies started to look for new suppliers. Thus, the research question is whether by building closer cooperation with Azerbaijan, Kazakhstan and Turkmenistan the EU is strengthening its energy policy.
Energy Security of European Union: cooperation with Azerbaijan, Kazakhstan and Turkmenistan
Keywords: Politikas zinātne (politoloģija)